2023
DOI: 10.1101/2023.02.02.526901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivophotopharmacology with light-activated opioid drugs

Abstract: Traditional methods for site-specific drug delivery in the brain are slow, invasive, and difficult to interface with recordings of neural activity. Here, we demonstrate the feasibility and experimental advantages of in vivo photopharmacology using caged opioid drugs that are activated in the brain with light after systemic administration in an inactive form. To enable bidirectional manipulations of endogenous opioid receptors in vivo, we developed PhOX and PhNX, photoactivatable variants of the mu opioid recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The existing literature on dopamine release in chronic opioid models is rife with contradictions and methodological caveats. Some work has found diminished responses that align with the traditional views of opioid tolerance (Mazei-Robison et al, 2011;McClain et al, 2023) while others have observed unchanged dopamine tone (Pothos et al, 1991) or even sensitization when responses in the NAc core are measured (Lefevre et al, 2020). The contrast of all these data highlights the ever-present trade-offs between mechanistic specificity and human relevance in our models and emphasizes the need to approach these questions with multiple experimental strategies.…”
Section: The Mechanisms Of Opioid Tolerance In the Nac Still Require ...mentioning
confidence: 81%
“…The existing literature on dopamine release in chronic opioid models is rife with contradictions and methodological caveats. Some work has found diminished responses that align with the traditional views of opioid tolerance (Mazei-Robison et al, 2011;McClain et al, 2023) while others have observed unchanged dopamine tone (Pothos et al, 1991) or even sensitization when responses in the NAc core are measured (Lefevre et al, 2020). The contrast of all these data highlights the ever-present trade-offs between mechanistic specificity and human relevance in our models and emphasizes the need to approach these questions with multiple experimental strategies.…”
Section: The Mechanisms Of Opioid Tolerance In the Nac Still Require ...mentioning
confidence: 81%